KOR I TEATR - WACHOWSKI, JACEK (Slavia Occidentalis, 2020)
The article is an attempt at characterizing the connections between KOR (the Workers’ Defense Committee, established by a group of Polish oppositionists in June 1976) and theatrical practice. Theatrical references are mentioned together with the prevailing literary –regerences in two areas: biographical (the founders of the movement were writers, poets, songwriters, and actors) and ideological. The biographical area also serves as an introduction to the other perspective which can be referred to as ideological. The theatre became a breeding ground for thoughts defying the communist reality. It was a meeting place for the broadly defined opposition, a cradle of ideas hostile to the system based on “workers and peasants” and the alliance with the Soviet Union. The resulting works included politicized performances of the classics as well as performances presented by alterative groups: Teatr Ósmego Dnia: Teatr 77, Jedynka, Provisorium and Teatr Stu. KOR’s activity from 1976 to the beginning of martial law introduced on 13 December 1981 clearly shows that the links between the revolutionary movement and the theater were an important feature of dissident activity and helped to reinforce and popularize its ideological values.